Organizational and Economic Efficiency of Microcredit Institutions in Selected European Countries - Monika ZIOLO; Lidia LUTY (Communications of International Proceedings, 2020)
The presence of financial institutions offering microloans has significantly improved access to external sources of financing for SMEs. Microfinance is now considered to be an innovative socio-economic tool to fill a gap in the financial market to combat social and financial exclusion. The aim of the article is to present the differences among the European countries in terms of activity in the field of microfinance. In the process of creating a synthetic measure of the assessment of the phenomenon, a synthetic variable defined in the TOPSIS method was used. The demand for microfinance services in Europe is steadily growing and there is a considerable potential for further growth in the years to come, as shown by the growth in the volume of microcredit granted. As the micro-enterprises take efforts to settle their liabilities to financial institutions on a regular basis, the percentage of non-performing loans and credit losses in most of the countries presented is relatively low. In the future, the fees and interest rates on microcredits should be modified, as in many countries they are higher for SME than for the traditional borrowers.
Keywords: financial efficiency; microcredits; European union countries